Optimization and Comparative Economic Analysis of Standalone and Grid-Connected Hybrid Renewable Energy System for Remote Location - Jain, Siddharth; Sawle, Yashwant (Frontiers in Energy Research, 2021)
Decentralized power generation in remote regions has become the primary requirement of society, based on renewable energy. Particularly in comparison with the electrification of urban areas, rural electrification is quite expensive. Microgrids' development utilizing hybrid power is a potential solution for the electrification of rural regions where the transmission chain of the network’s extension is unfeasible or inefficient. This economically effective solution ensures system stability and energy security in a stand-alone microgrid system with environmentally friendly hybrid sources. This research aims to structure a power generation model associated with different HRES combinations using a HOMER software application at a location in India. This research's primary goal is to examine the foremost possible HRES configuration utilizing various variations to meet the requirement for village load in a secure, permanent and sustainable way. As a result of this study, it is seen that NPC, O&M, COEs, RF of on-grid energy systems are better than off-grid energy systems. In the study, between eight hybrid system combinations, the lowest COE of 0.034 $/kWh is obtained with the PV-WT-MH-GRID-CT system in the on-grid scenario.This analysis shows NPC, COE, O&M, and renewable fraction are sensitive to the variation in all the considered sensitivity parameters.